From Environmental Toxicants to Antibacterial Agents: BPA Analogues Selectively Inhibit the Growth of Gram-Positive Bacteria by Disturbing Biosynthesis of the Cell Wall - Cao, Huiming; Li, Zhunjie; Chen, Bolei; Wang, Jing; Zhou, Zhen; Li, Zhi; Qian, Yun; Liang, Yong (Environment & health (Washington, D.C.), 2023)
Remarkable antibacterial activity of BPA analogues especially for tetrabromobisphenol A against 25923 (Sa25923) and methicillin-resistant (MRSA) has been reported in our previous studies. However, the toxic effects of the compounds as environmental contaminants on the endocrine system limited their applications in the field of medicine and health. Given the abuse of antibiotics has led to the emergence of multiple super-resistant bacteria, we considered that structural modifications based on the BPA structure will be available for molecular designing of potential antimicrobial agents without drug resistance. In this study, to further improve the antibacterial activity and reduce the biological toxicity, we performed the computational models to evaluate the binding affinities of BPA analogues to the potential target DltA protein in the biosynthesis of cell wall. A series of synthesized achiral analogues of α,α,α'-tris(4-hydroxyphenyl)-1-ethyl-4-isopropylbenzene (α,α,α'-TEIB) exhibited low minimum inhibitory concentration against Sa25923 and MRSA (2 or 1 μg mL ). Especially, the analogue A4 did not induce the drug-resistant mutants for all tested Gram-positive bacterial strains and exhibited relatively lower cytotoxicity in HepG2 cells. The developed classification model based on the light gradient boosting algorithm showed the superior performances on the internal robustness and generalization ability for the ligand-based virtual screening of bisphenol and polyphenol antimicrobial substances. Collectively, our findings suggest that the molecular structure of α,α,α'-TEIB is promising as a scaffold, which is expected to achieve a breakthrough in the development of antibiotics which can prevent the invasion of MRSA and other super bacteria.